Pengaruh Motivasi dan Pengembangan Karir Serta Softskill Terhadap Kinerja Karyawan - Andy Hakim (Journal of Business and Economics Research (JBE), 2021)
Technology developments make it easier for companies in the managerial process to find out strategies and techniques for survival, the sustainability and growth of the company's life depends on the availability of resources that the company has, especially human resources which are the most valuable main component in every activity and activity of a company, the importance of knowing the quality performance of human resources in the company or commonly referred to as employees to assist company management in achieving company goals needs to be changed and improved employee performance to the company, this results in the need to know the influences and factors that can affect employees in improving employee performance, in looking at several factors that affect the performance of employees in this study such as the influence of motivation, career development and soft skills possessed by employees, data from respondents, namely employees are processed using S PSS to facilitate the stages of finding the effect on each variable. The results found in the form of the influence of the variable motivation and career development have a high significant value and have a positive effect while the value of soft skills has a negative influence